2010
DOI: 10.1188/10.cjon.598-606
|View full text |Cite
|
Sign up to set email alerts
|

Insurance-Related and Financial Challenges Reported by Managed Care Enrollees With Breast Cancer

Abstract: Cancer survivors in the United States often encounter significant challenges in obtaining and paying for medical care. Multiple research studies have examined these issues in Medicare and Medicaid populations and the underinsured, but very little is known about insurance-related challenges encountered by cancer survivors enrolled in private insurance programs such as managed care. This secondary analysis of data explored the insurance-related and financial challenges reported by women enrolled in a managed car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…As in other studies (Klimmek et al, 2010; Mathews & Park, 2009), few participants reported having discussed financial limitations related to treatment with their providers. Men were particularly unlikely to admit to or raise issues of financial inadequacies or difficulties.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As in other studies (Klimmek et al, 2010; Mathews & Park, 2009), few participants reported having discussed financial limitations related to treatment with their providers. Men were particularly unlikely to admit to or raise issues of financial inadequacies or difficulties.…”
Section: Discussionmentioning
confidence: 62%
“…Patients have identified cancer costs as contributing to treatment barriers, increasing stress, and decreasing quality of life (Klimmek, Snow, & Wenzel, 2010; Wagner & Lacey, 2004). The high cost of cancer treatment is borne by patients and caregivers (Chang et al, 2004; Mathews & Park, 2009) and may be a greater barrier to treatment for African Americans (Chu, Miller, & Springfield, 2007; Mosavel & Sanders, 2011) with significant societal consequences (Adler & Page, 2008).…”
mentioning
confidence: 99%
“…The inability of predicting out-of-pocket costs is frustrating to cancer patients [28]. This may explain the weight given by our participants to the need of having information upfront about costs and resources available to deal with them.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unique to this group of participants. Other breast cancer survivors on managed care, for example, reported stress and frustration related to the considerable challenges in dealing with their insurance companies during and after treatment [28]. Challenges were related to understanding written information, obtaining authorizations for care or assistance with insurance-related tasks, paying bills that kept coming, as well as planning for the cost of their care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation